Constraints on the dynamics of mantle plumes from uplift of the Hawaiian Islands - Zhong, S; Watts, A (2002)
The ~0.2 mm/yr uplift of Hawaiian islands Lanai and Molokai and Hawaiian swell topography pose important constraints on the structure and dynamics of mantle plumes. We have formulated 3-D models of mantle convection to investigate the effects of plume-plate interactions on surface vertical motions and swell topography. In our models, the controlling parameters are plume radius, excess plume temperature, and upper mantle viscosity. We have found that swell height and swell width constraints limit the radius of the Hawaiian plume to be smaller than 70 km. The additional constraint from the uplift at Lanai requires excess plume temperature to be greater than 400 K. If excess plume temperature is 400 K, models with plume radius between 50 and 70 km and upper mantle viscosity between 1020 and 3×1020 Pa s satisfy all the constraints. Our results indicate that mantle plume in the upper mantle may be significantly hotter than previously suggested. This has important implications for mantle convection and mantle melting. In addition to constraining plume dynamics, our models also provide a mechanism to produce the observed uplift at Lanai and Molokai that has never been satisfactorily explained before. © 2002 Elsevier Science B.V. All rights reserved.